2020
DOI: 10.1186/s12884-020-03195-1
|View full text |Cite
|
Sign up to set email alerts
|

Trends and correlates of maternal, newborn and child health services utilization in primary healthcare facilities: an explorative ecological study using DHIMSII data from one district in the Volta region of Ghana

Abstract: Background Sustainable Development Goal 3 aims at reducing global neonatal mortality to at least 12 per 1000 livebirths, under-five mortality to at least 25 per 1000 livebirths and maternal mortality ratio to less than 70 per 100,000 livebirths by 2030. Considering the achievement so far, many countries in sub-Saharan Africa, including Ghana are not likely to achieve these targets. Low utilization of maternal, newborn and child health (MNCH) services partly account for this predicament. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The proportion of mothers achieving adequate ANC (4-7 ANC visits) increased from 49.3% in 2006 to 49.98% in 2011 to 58.61% in 2017-2018. Consistent with this study, Alhassan and colleagues found that there has been an increase in the trends of ANC service utilization in Ghana in the past decade [ 27 ]. This may be due to the enactment and implementation of the Ghana National Health Insurance Scheme (NHIS) in 2003 which aimed to offer free medical care to pregnant women.…”
Section: Discussionsupporting
confidence: 82%
“…The proportion of mothers achieving adequate ANC (4-7 ANC visits) increased from 49.3% in 2006 to 49.98% in 2011 to 58.61% in 2017-2018. Consistent with this study, Alhassan and colleagues found that there has been an increase in the trends of ANC service utilization in Ghana in the past decade [ 27 ]. This may be due to the enactment and implementation of the Ghana National Health Insurance Scheme (NHIS) in 2003 which aimed to offer free medical care to pregnant women.…”
Section: Discussionsupporting
confidence: 82%
“…The ambitious SDG agenda may not be achieved in many SSA countries including Mali 5 if the utilisation of maternal healthcare components such as ANC, SBA and PNC is not accelerated. 26 There is, however, a paucity of empirical literature on the state of maternal healthcare utilisation (ANC, SBA and PNC) at the national level in the country. Such data are needed for the acceleration of interventions to improve utilisation, reduce maternal mortality and accelerate progress towards achievement of the SDGs.…”
Section: Introductionmentioning
confidence: 99%
“…The ambitious SDG agenda may not be achieved in many SSA countries including Mali 5 if the utilisation of maternal healthcare components such as ANC, SBA and PNC is not accelerated 26. There is, however, a paucity of empirical literature on the state of maternal healthcare utilisation (ANC, SBA and PNC) at the national level in the country.…”
Section: Introductionmentioning
confidence: 99%
“…The level of education of the spouse and ANC attendance was connected with institutional delivery studies in Nigeria, Ghana and SSA reported on intervention to improve the majority of the health system, with an increase in frontline health staff and retention strategies, as well as investments in universal coverage to increase ANC and SBD utilization services [71,124,176]. Atake, 2018 in Togo, reported that a significant number of migrant mothers utilised ANC services in Togo compared to non-migrant women due to health insurance, which provides more financial protection to migrant mothers [161] [68] with ANC visits.…”
mentioning
confidence: 99%